(untitled) (Czech Journal of International Relations, 2000)
The commitment of the contracting parties to liquidate chemical weapons and all premises used for their manufacture by the year 2007 is the fundamental pillar of the Agreement un Banning the Development, Manufacture, Stockpiling and Use of Chemical Weapons and their destruction (hereafter only Agreement). This is the first multilateral disarmament agreement which bans an entire category of weapons of mass destruction while at the same time it stipulates measures to control the way this commitment is being respected. The Agreement is universal since it bans not only the actual utilization or threat to use chemical weapons but also their development, manufacture, acquisition and stockpiling. Under the Agreement, the direct or indirect proliferation of chemical weapons is illegal, as is the utilization of chemical weapons including the possibility of a retaliatory strike, military preparations with the aim of using chemical weapons as well as assistance, support or inciting any type of banned activity. This year, the Agreement will have been in force for three years which is the time limit set for the liquidation of 1% of all stocks of the chemical weapons in the possession of each contracting state. The time limit for the liquidation of alt chemical weapons is ten years from the time the Agreement came in to force. The authors of this essay deal in detail with the present state of the liquidation of the chemical arsenal of the United States and the Russian Federation. They arrive at the conclusion that at present the US is the only state with extensive practical experience with the safe liquidation of chemical weapons, and this without an adverse influence on the environment. Yet it is not possible to say whether the US will be capable of fulfilling the final deadline of the liquidation of chemical weapons. The situation in Russia, on the contrary, is far more complicated since already now the programme of liquidation is at least two years behind schedule. And in view of the shortage of its own financial resources, it is evident that Russia will not be capable of liquidating its chemical weapons stocks within the required time limit without more extensive international assistance. In addition, the authors turn their attention in the essay to a number of other issues, directly connected with the liquidation of chemical weapons, such as the demands of the liquidation of chemical weapons, stipulated by the Agreement, or former methods of the liquidation of chemical weapons and their influence 0n the environment.